Hydrodynamic Modelling For Flood Damage Assessment Of Sungai Tupai, Taiping, Perak - Ahmad, Baharudin (2015)
In the past, flood losses or damages can only be determined after the incident. However, with the development of information technology, especially computer technology, a flood can be modelled using desktop computer and estimation of damages and losses due to flooding can be assessed quicker or even before the flooding occurs. The combination of 1D modelling techniques in the river channels and 2D on floodplains balanced the time required to build the model and accuracy of the simulation. With the advancement of Geographical Information System (GIS) technology, simulation results can be analyzed and presented in a more visually appealing manner. The objective of this study is to produce flood maps through computer modeling technique, determine the area involved and further assess the losses that may be encountered. The area selected for this study is Tupai River with a catchment area of approximately 950 hectares and 7.5km in length of Tupai River that includes residential and industrial areas and served as one of the Taiping City drainage system. Finding from the study reveals that in 100 years Average Recurrence Interval of Rainfall, only 119 percent of the total catchment area of Tupai River inundated with flood waters. Total losses estimated using the method introduced by JICA (1995) is approximately RM700,000.00 that involved 303 houses and 1333 resident.